Effects of agricultural practices on foraging habitats of a seabird species in the Baltic Sea - Garthe, Stefan; Schwemmer, Philipp; Kubetzki, Ulrike; Heinze, Bernd (Ecology and Evolution, 2022)
Omnivorous and opportunistic species may be good indicators of food availability. Gulls often use human-impacted landscapes and may respond to changes by altering their feeding ecology. We investigated the foraging behavior of individual common gulls (Larus canus), focusing on their distribution during foraging and their selected habitat types. We tracked adult common gulls using GPS telemetry at their largest breeding colony in the southwestern Baltic Sea, Germany. Foraging habitats were analyzed from tracking data for three breeding seasons 2016, 2017, and 2019 and were compared with potentially available foraging habitats. Most breeding birds flew toward terrestrial areas. Feeding sites were located on average 11.7-14.3 km from the colony (range 0.9-36.5 km). Corn and sugar beet fields were used significantly and extensively compared with their availability in 2016 and 2017, while wheat, rape, and barley fields were used significantly less. Data from 2019 suggested seasonal shifts in habitat use. Birds spent between 30 and 1300 min per week at their preferred feeding sites, with significant differences between the major habitats selected. We found a stable, clear, multiyear pattern in common gull foraging behavior in relation to agricultural practices. Fields with little or no crop cover and thus access to the soil were preferred over fields with high crop cover. These results suggest that local food availability may be limiting further population increases in this species.